Evaluasi Hasil Labioplasti Menggunakan Skor CLEFT-Q - Deki, Feldy; Hatibie, Mendy; Oley, Maximillian Ch.; Langi, Fredrik G. (e-CliniC, 2021)
Abstract: Application of CLEFT-Q score instrument in the assessment of surgical outcomes for cleft lip and/or cleft palate based on patient reports is still relatively new. This study was aimed to establish the normative value of the Indonesian version of CLEFT-Q score in post-cleft lip surgery patients and to differentiate the results of cleft lip surgery according to the score based on the type of cleft, age, and sex. This was a preliminary study using the Indonesian CLEFT-Q instrument. Patients were interviewed for filling out the Indonesian version of CLEFT-Q after surgery. There were 75 samples in this study. Significant results were found in the association between age and CLEFT-Q score (p<0.05 and R>0.35). Variable selection for multi-variable analysis included cleft type and age in the model, where age alone indicated a significant relationship. The linear regression model involved the relationship between CLEFT-Q scores and gender, age, and cleft type as covariates. The correlation shown was classified as having moderate strength (R=0.46) for all covariates. In conclusion, the normative value of the Indonesian version of CLEFT-Q score with an approach to post-cleft lip surgery patients got a value that was in accordance with the highest standard in the literature, namely 91. The results of cleft lip surgery according to the Indonesian version of CLEFT-Q score based on the type of cleft, age and gender can be applied according to the literature.Keywords: cleft lip; cleft palate; cleft lip and palate; Indonesian version of CLEFT-QÂ Abstrak: Penerapan skor CLEFT-Q dalam penilaian luaran operasi bibir sumbing dan/atau langit-langit terbelah berdasarkan laporan pasien masih relatif baru. Penelitian ini bertujuan untuk mene-gakkan nilai normatif skor CLEFT-Q berbahasa Indonesia pada pasien pasca operasi bibir sum-bing serta membedakan hasil operasi bibir sumbing menurut skor tersebut berdasarkan tipe cleft, usia, dan jenis kelamin. Jenis penelitian ialah studi pendahuluan penggunaan CLEFT-Q berbahasa Indonesia. Pasien diwawancarai untuk melakukan pengisian CLEFT-Q berbahasa Indonesia setelah operasi. Hasil penelitian mendapatkan total 75 sampel. Hasil bermakna ditemukan pada hubungan antara usia dan skor CLEFT-Q (p <0,05 dan R > 0,35). Seleksi variabel untuk analisis multivariabel mengikutsertakan tipe cleft dan usia di dalam model, dan variabel usia saja yang mengindikasikan adanya hubungan bermakna (95% CI 1,15-2,33; p=0,006). Model regresi linear melibatkan hubungan antara skor CLEFT-Q dengan jenis kelamin, usia, dan tipe cleft sebagai kovariat dan mendapatkan korelasi kekuatan sedang (R=0,46) untuk semua kovariat. Simpulan penelitian ini ialah nilai normatif skor CLEFT-Q berbahasa Indonesia dengan pendekatan terhadap pasien pasca operasi bibir sumbing mendapatkan nilai yang sesuai dengan standar tertinggi pada kepustakaan yaitu 91. Hasil operasi bibir sumbing menurut skor CLEFT-Q berbahasa Indonesia berdasarkan tipe cleft, umur dan jenis kelamin dapat diterapkan sesuai kepustakaan.Kata kunci: cleft lip; cleft palate; cleft lip and palate; skor CLEFT-Q berbahasa Indonesia